2014
DOI: 10.1504/ijmsi.2014.067115
|View full text |Cite
|
Sign up to set email alerts
|

Fluid viscous damper in mitigation of structural vibration effect due to underground blast

Abstract: Blast induced ground vibration, caused by underground explosions, can result in substantial damage to nearby structures. In the present study, an investigation is made on the possible reduction of structural vibration effect due to underground blast by using the fluid viscous damper (FVD). The blast load is modelled by an exponentially decaying function representative of a typical rock blast. The cylindrical pot FVD is considered for which the fractionalderivative Maxwell model is adopted. The dynamic response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Miyamoto and Taylor (2000) evaluated the effectiveness of an FVD under blast loading and demonstrated that structures equipped with an FVD provide an effective way to control the blast response of the structure. Mondal et al (2014) showed the effectiveness of an FVD in reducing peak structural displacement under underground explosions. These researches have been focused on only the blast performance of the FVD when this control system is originally employed for controlling the structures under seismic loading and its seismic performance should also be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Miyamoto and Taylor (2000) evaluated the effectiveness of an FVD under blast loading and demonstrated that structures equipped with an FVD provide an effective way to control the blast response of the structure. Mondal et al (2014) showed the effectiveness of an FVD in reducing peak structural displacement under underground explosions. These researches have been focused on only the blast performance of the FVD when this control system is originally employed for controlling the structures under seismic loading and its seismic performance should also be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…|xU}=kt 'Q=Hiv= Q=@ 'RwmU}w Qo = Q}t '|}xRQr Qo =OH '|vD@ |xR=U %|O}rm u=oS=w "OQmrta xtOkt "1 pLt R= XNWt |xrY=i =@ |}x]kv QO u; |Q=oOv=t w Q}F -=D u=tR COt w QwmPt Gwt l} QO Q=Hiv= |=v@t Q@ |}=OD@= C=ar=]t "CU= xDiQo CQwY |O=}R C=ar=]t 'Q=Hiv= xDiQo CQwY 'OwW|t xDio |wQm Gwt =@ Q=Hiv= =yu; x@ Kq]Y= QO xm =wy R= x]kv QO [1] "CU= xOW x=Q= u; pLt R= xrY=i w xQHivt |xO=t u= R}t |=v@t Q@ |]@=wQ w Q=F; u}vJty w OvwW|t xO}t=v |wQms}v xm u}tR QO |Q=Hiv= |=yQF= '|Oa@ C=ar=]t O=tDa= p@=k OwHwt |=yxt=vu}}; [2] "Ov=xOW |UQQ@ p}=t Kw]U =@ Q=Hiv= Gwt OQwNQ@ [3] '=m}Qt; VDQ= u=UOvyt |=yxt=vu}}; %R= OvDQ=@a Q=Hiv= Q=@ u}tND |xv}tR QO xR=U Q@ OQ=w |m}t=v}O Q=F; |UQQ@ CyH QO " [4] =B wQ= |x}O=LD= Q}N= |xt=vu}}; w =@ u= QoWywSB |NQ@ "CU= xDiQo CQwY |mOv= Q=}U@ C=ar=]t 'Q=Hiv= Gwt QF= QO "Ov=xOQm |UQQ@ = Q QwmPt Q=F; '|y=oW}=tR; OQ=wt |[a@ QO w |OOa |=y|R=UpOt = Q pmW |}xkQw |=yxR=U QO Q=Hiv= QF= '2001 u= Q=mty w wDv}U=H 'xvwtv |= Q@ Q}Ut QO |Oqwi |xLiY l} uO=O Q= Qk w |awvYt Q=Hiv= O=H}= =@ w OvOQm |UQQ@ w |Q}oxR=Ov= xLiY |wQ Q@ = Q Q=Hiv= R= pY=L |=yQ=Wi 'Q=Hiv= R= pY=L Gwt x@ w Ov=xOQm xU}=kt |OOa |R=UpOt =@ = Q jQw QO xOt; OwHw x@ |=yMU=B u}vJty [5] "Ov=xO=O x=Q= xR=U |wQ Q@ Q=Hiv= Gwt R= pY=L Q=Wi |= Q@ = Q |]@=wQ ? }DQD u}= Ovr@ |xR=U l} |OOa pOt |UQQ@ [14] "O=O Vy=m |}=Q}t V}=Ri= =@ |OwOL =D u=wD|t = Q xv}W}@ xOW |UQQ@ Q=Hiv= Q=@ CLD xR=U |=yMU=B QO RwmU}w Qo = Q}t QF= xm '2014 =@ |@ wN x@ xR=U |=yMU=B C=a@Qt u}ov=}t xm OQm xOy=Wt u=wD|t |@ wN x@ 'CU= |O=}R Cw=iD CaQU w ?=DW |xrk u= R}t |rw &Ov=xOW xO=O Vy=m |}=Q}t V}=Ri= u=wD|t u; ltm x@ xm OQ=O OwHw |Q=Okt 'u}vJty "CU= xDW=Ov |}=Q}t C= Q}}eD =@ QO |ivt |QF= |}=Q}t 'QDW}@ u; R= |rw 'Ov=UQ xv}W}@ u= R}t x@ = Q ?=DW Vy=m [15] "CW=Po Oy=wN…”
mentioning
confidence: 99%